Sustainable Construction Materials 2012 2012
DOI: 10.1061/9780784412671.0021
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Crumb Tire Rubber-Modified Hot Mix Asphalt Concrete in Sudan

Abstract: Scrap tires form a major part of the world's solid waste management problem. In recent years, the waste tire problem has become so acute that there is an urgent need to find an optimum and effective way to use scrap tires in asphalt mixtures. This paper investigates used tire rubber as an asphalt modifier and its potential prospects to enhance bitumen physical and asphalt mixture properties in hot climate like Sudan. Bitumen grade 60/70 blended with different percentage of crumb used tire rubber. Engineering a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
1
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 3 publications
(1 reference statement)
1
1
0
Order By: Relevance
“…Softening point values increase with aging time as indicated in fig.4. When Crumb rubber was added to asphalt cement, the softening point increases as rubber content increases, such results agree with and (Osman & Adam 2012) findings. The ductility of asphalt cement without additive was (+100 mm).…”
Section: Effect Of Rubber and Aging On Physical Properties Of Asphaltsupporting
confidence: 90%
“…Softening point values increase with aging time as indicated in fig.4. When Crumb rubber was added to asphalt cement, the softening point increases as rubber content increases, such results agree with and (Osman & Adam 2012) findings. The ductility of asphalt cement without additive was (+100 mm).…”
Section: Effect Of Rubber and Aging On Physical Properties Of Asphaltsupporting
confidence: 90%
“…Hence, the pavement that is incorporated https://doi.org/10.31436/iiumej.v25i1.2969 with crumb rubber will be less likely to go through any deterioration due to hot climatic weather such as rutting. This conclusion can also be supported by the authors of [6], as the authors mentioned on the research paper that the results of inclining softening point value with increment of percentage of crumb rubber indicate that pavements that is constructed using CRMB would be less susceptible to traffic deformation distress at high temperatures compared to conventional asphalt pavements. According to [11], high softening point was desirable for hot and warm climates application.…”
Section: Softening Pointsupporting
confidence: 53%
“…According to the previous research executed by the authors of [2] and [15], the value of the Marshall stability and stiffness should be enhanced as the percentage of crumb rubber replacement increases, however the result of this research shows a different outcome especially for the dense mixture. Nonetheless, the authors of [6] stated in the findings that the reduction in the value of Marshall stability and stiffness after the introduction of crumb rubber to the mixture may happen due to lack of adhesion between the aggregates. This may occur as with higher crumb rubber percentage, the binder would become more viscous and less workable.…”
Section: Marshall Stability Flow and Stiffnessmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the high-viscosity of the rubberized binder and the presence of rubber particles in the bituminous matrix, the rubberized DG HMAs have a slightly higher bitumen content compared to DG mixtures with either neat or other polymer-modified binders. In most of the cases, it has been found that the superior performance of the rubberized bitumen improved the thermo-mechanical response of the mixtures compared to traditional HMAs [21,22].…”
Section: Introductionmentioning
confidence: 99%